2008
DOI: 10.1183/09031936.00010407
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterisation of T-lymphocytes in COPD: abnormal CD4+CD25+ regulatory T-lymphocyte response to tobacco smoking

Abstract: Tobacco smoking induces an inflammatory response in the lungs of all smokers but, for reasons that are still poorly understood, only a proportion of them develop chronic obstructive pulmonary disease (COPD). Recent evidence indicates that this inflammatory response persists after smoking cessation, suggesting some type of auto-perpetuation mechanism similar to that described in autoimmune disorders. T-lymphocytes (CD4+ and CD8+) have been implicated in the pathogenesis of both COPD and several autoimmune proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
127
2
14

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 169 publications
(163 citation statements)
references
References 32 publications
20
127
2
14
Order By: Relevance
“…Previous studies have characterised T-regulatory cells from bronchoalveolar lavage fluid (BALF), dispersed lung cells and peripheral blood [6,13,14]. The major finding was that CD4 +…”
Section: This Is the First Study To Quantify And Describe The Localismentioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have characterised T-regulatory cells from bronchoalveolar lavage fluid (BALF), dispersed lung cells and peripheral blood [6,13,14]. The major finding was that CD4 +…”
Section: This Is the First Study To Quantify And Describe The Localismentioning
confidence: 94%
“…T-regulatory markers including FOXP3 have been used to show that smokers have increased numbers of T-regulatory cells in bronchoalveolar lavage fluid [13,14] compared with nonsmokers. One of these studies also showed decreased Tregulatory numbers in COPD patients compared to smokers with normal lung function, suggesting decreased T-regulatory function in COPD.…”
mentioning
confidence: 99%
“…IL-2, which plays a critical role in the development and homeostasis of Treg cells, 39 is elevated in COPD patients who show disease stability, 40 inducing dominant upregulation of Treg cells in smokers with preserved lung function compared with COPD patients. 41 As our previous studies demonstrated that sγc inhibits IL-2 signaling, 22 excessive T cell response with IL-2-induced Treg cells. On the other hand, Treg development depends on IL-2 and TGFβ, which is also linked to Th17 differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…CD8+ T-cells were mature cells characterised by a high CD45RA/CD45R0 ratio. Compared with never-smokers, smokers with normal lung function showed a prominent upregulation of T-regulatory cells that was absent in patients with COPD [73]. Recruitment of CD8+ T lymphocytes may be triggered chemokines secreted by the epithelium of small conducting airways.…”
Section: Distal Airways Inflammation In Copdmentioning
confidence: 99%